Collections of Stained Glass and their Histories Glasmalerei-Sammlungen und ihre Geschichte Les collections de vitraux et leur histoire : Transactions of the 25th International Colloquium of the Corpus Vitrearum in Saint Petersburg/Akten des 25. Internationalen Kolloquiums des Corpus Vitrearum in Sankt Petersburg/Actes du 25e Colloque International du Corpus Vitrearum à Saint-Pétersburg. - Ayers, Tim (Peter Lang AG, Internationaler Verlag der Wissenschaften, 2013)
At the 25th International Colloquium of the Corpus Vitrearum, which took place in one of the greatest of all museums, The Hermitage in St. Petersburg, the researchers of many countries discussed stained glass collections for the first time. The present conference transactions, published in the three official languages of the international Corpus Vitrearum, are dedicated to the reawakening of interest in ancient stained glass from the late eighteenth century. The contributions are concerned partly with the creation of collections and the motives of their collectors, but also with the odyssey of various panels and groups of windows. Other studies address wider aspects of the history of collections and the museum display of stained glass. Anlaesslich des 25. Internationalen Kolloquiums des Corpus Vitrearum, das in einem der groessten und bedeutendsten Museen der Welt, der Staatlichen Eremitage in Sankt Petersburg, stattfand, wurden Glasmalereisammlungen erstmals von einer internationalen Autorengruppe des Corpus Vitrearum breit diskutiert. Die Beitraege in den drei offiziellen Sprachen des Corpus Vitrearum behandeln das wiedererwachte Interesse an alter Glasmalerei. Die Autoren widmen sich der Entstehung bestimmter Sammlungen, der Motivation der Sammler, oder aber der Odyssee ausgewaehlter Denkmaeler sowie sammlungsgeschichtlichen Aspekten bis hin zu Fragen der musealen Praesentation von Glasmalereien. Lors du 25e Colloque international du Corpus Vitrearum qui a eu lieu a l'Ermitage de Saint-Petersbourg, un des plus grands et des plus prestigieux musees, les chercheurs venus de nombreux pays ont discute pour la premiere fois des collections de vitraux. Les contributions aux actes du colloque, publiees dans les trois langues officielles du Corpus Vitrearum international, sont consacrees au reveil de l'interet pour le vitrail ancien. Les articles sont